PENGARUH SERVICE QUALITY DAN PRODUCT QUALITY TERHADAP COSTUMER SATISFACTION PADA USAHA SAPPO DRINKS CABANG 5 KOTA SENGKANG (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to determine the effect of Service Quality and Product Quality on Customer Satisfaction in the Sappo Drinks Business, Branch 5, Sengkang City. This study used 310 respondents from Puangrimaggalatung university students. The instrument used in this research is a questionnaire. Hypothesis testing was carried out using multiple linear regression analysis with the help of SPSS 26. The results of this study explain that there is a simultaneous effect of Service Quality and Product Quality on Customer Satisfaction in the Sappo Beverage Business Branch 5 Sengkang City.